2002
DOI: 10.1089/088922202753394736
|View full text |Cite
|
Sign up to set email alerts
|

Human Retroviruses (HIV and HTLV) in Brazilian Indians: Seroepidemiological Study and Molecular Epidemiology of HTLV Type 2 Isolates

Abstract: To investigate serological, epidemiological, and molecular aspects of HTLV-1, HTLV-2, and HIV-1 infections in Amerindian populations in Brazil, we tested 683 and 321 sera from Tiriyo and Waiampi Indians, respectively. Both HIV-1 and HTLV-2 infections were detected at low prevalence among the Tiriyos whereas only HTLV-1 was present among the Waiampis, also at low prevalence. Analysis of the nucleotide sequence of the 631 bp of the env gene obtained from the three HTLV-2 isolates detected among the Tiriyos demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
11

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 43 publications
4
48
0
11
Order By: Relevance
“…HTLV-II has been shown to be endemic among various American Indian populations, including Navajos and Pueblos (New Mexico) (Hjelle et al, 1993) and Seminoles (Florida) (Biggar et al, 1996;Levine et al, 1993) in North America and the Guaymi in Panama (Lairmore et al, 1990;Pardi et al, 1993). In South America, a number of distinct populations in Colombia (Wayu, Guahibo, and Tunebo groups) Switzer et al, 1995), Argentina (Toba and Mataco) (Biglione et al, 1999), and Brazil (Kayapó and Krahô) (Black et al, 1994;Shindo et al, 2002) have been found to be infected with this virus. HTLV-II infection has also been endemic for the past 10-20 years among intravenous drug users in Europe, especially in Italy , Spain (Soriano et al, 1993), and Ireland, as well as in North America (Hall et al, 1992;Lee et al, 1989;Murphy et al, 1998;Schwebke et al, 1994).…”
Section: Human T-cell Lymphotropic Viruses Types I (Htlv-i) and Typementioning
confidence: 99%
“…HTLV-II has been shown to be endemic among various American Indian populations, including Navajos and Pueblos (New Mexico) (Hjelle et al, 1993) and Seminoles (Florida) (Biggar et al, 1996;Levine et al, 1993) in North America and the Guaymi in Panama (Lairmore et al, 1990;Pardi et al, 1993). In South America, a number of distinct populations in Colombia (Wayu, Guahibo, and Tunebo groups) Switzer et al, 1995), Argentina (Toba and Mataco) (Biglione et al, 1999), and Brazil (Kayapó and Krahô) (Black et al, 1994;Shindo et al, 2002) have been found to be infected with this virus. HTLV-II infection has also been endemic for the past 10-20 years among intravenous drug users in Europe, especially in Italy , Spain (Soriano et al, 1993), and Ireland, as well as in North America (Hall et al, 1992;Lee et al, 1989;Murphy et al, 1998;Schwebke et al, 1994).…”
Section: Human T-cell Lymphotropic Viruses Types I (Htlv-i) and Typementioning
confidence: 99%
“…HTLV-2 is prevalent in native populations, such as indigenous peoples in the Americas and Pygmy tribes in Africa, and in intravenous drug users [15][16][17][18][19] . Despite a 65% homology with HTLV-1, HTLV-2 has not been consistently associated with human disease; however, neurological disorders similar to HAM/TSP have been observed in patients with HTLV-2 infection 15,20 .…”
Section: Introductionmentioning
confidence: 99%
“…The overall prevalence of severe HTLV-1-associated disease is 2 to 8% among HTLV-1-infected persons, estimated to represent 15 million to 25 million individuals worldwide. HTLV-2 has been shown to be endemic in various American Indian populations (2,3,33,41,43,44) and has also been endemic for the past 10 to 20 years among intravenous drug users in Europe and North America (32,39,40). In populations in which these viruses are endemic, HTLV-1 and HTLV-2 are transmitted between sexual partners and from mother to child during breast-feeding.…”
mentioning
confidence: 99%